2012
DOI: 10.1093/brain/aws152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of analgesics and sedatives on the occurrence of spreading depolarizations accompanying acute brain injury

Abstract: Spreading depolarizations are waves of mass neuronal and glial depolarization that propagate across the injured human cortex. They can occur with depression of neuronal activity as spreading depressions or isoelectric spreading depolarizations on a background of absent or minimal electroencephalogram activity. Spreading depolarizations are characterized by the loss of neuronal ion homeostasis and are believed to damage functional neurons, leading to neuronal necrosis or neurological degeneration and poor outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(183 citation statements)
references
References 37 publications
4
177
0
2
Order By: Relevance
“…Episodes of CSD have been shown to be sensitive to selective pharmacological treatments, including NMDA receptor and calcium antagonists. [151][152][153] Also, previous data have indicated that CSD episodes are sensitive to brain temperature. 154,155 Additional experimental and clinical data are therefore required to determine the incidence of CSD in various TBI patient populations and the testing of novel treatment strategies targeting episodes of PTE and CSD in patients who could benefit in terms of long-term outcomes.…”
Section: Post-traumatic Epilepsy and Cortical Spreading Depolarizationsmentioning
confidence: 98%
“…Episodes of CSD have been shown to be sensitive to selective pharmacological treatments, including NMDA receptor and calcium antagonists. [151][152][153] Also, previous data have indicated that CSD episodes are sensitive to brain temperature. 154,155 Additional experimental and clinical data are therefore required to determine the incidence of CSD in various TBI patient populations and the testing of novel treatment strategies targeting episodes of PTE and CSD in patients who could benefit in terms of long-term outcomes.…”
Section: Post-traumatic Epilepsy and Cortical Spreading Depolarizationsmentioning
confidence: 98%
“…SD-induced peak hyperemia (component II) is often smaller, and the initial hypoperfusion (component I) is more prominent, when resting CBF and vessel calibers are elevated (e.g., acetazolamide, inhalational anesthesia, dimethyl sulfoxide) than when they are reduced (e.g., barbiturate or propofol anesthesia, indomethacin, hypocapnia, or post-SD oligemia after a preceding SD) (71,95,257,394,460). Although anesthetics can alter SD susceptibility (74,191,200,240,241,375,404,443,466), they do not appear to have a consistent direct effect on the hemodynamic response (443); both absent and potent peak hyperemic responses have been reported in unanesthetized animals in different studies (95,424,443). Nevertheless, anesthesia can indirectly influence the hemodynamic response by changing resting CBF (128) or systemic blood pressure (see below).…”
Section: Potential Sources Of Heterogeneity In the Cbf Response To Sdmentioning
confidence: 99%
“…Ketamine, an NMDA antagonist, has a multitude of protective effects in vivo 38 , including the potential to prevent excitotoxicity to neurons, activate the mTOR pathway and release BDNF into the serum [39][40][41] . Ketamine has been reported to enhance neuronal survival following brain trauma in humans and reduce light injury in rodent photoreceptors 42,43 . Investigations into the mechanism of remote ischemic conditioning with awake blood pressure cuffing will avoid anesthetic confounds.…”
Section: Discussionmentioning
confidence: 99%